Depth-dependent artifacts resulting from ApRES signal clipping. Issue 81 (28th April 2020) - Vaňková, Irena; Nicholls, Keith W.; Xie, Surui; Parizek, Byron R.; Voytenko, Denis; Holland, David M.
Abstract: Several autonomous phase-sensitive radio-echo sounders (ApRES) were deployed at Greenland glaciers to investigate ice deformation. Different attenuation settings were tested and it was observed that, in the presence of clipping of the deramped ApRES signal, each setting produced a different result. Specifically, higher levels of clipping associated with lower attenuation produced an apparent linear increase of diurnal vertical cumulative displacement with depth, and obscured the visibility of the basal reflector in the return amplitude. An example with a synthetic deramped signal confirmed that these types of artifacts result from the introduction of harmonics from square-wave-like features introduced by clipping. Apparent linear increase of vertical displacement with depth occurs when the vertical position of a near-surface internal reflector changes in time. Artifacts in the return amplitude may obscure returns from internal reflectors and the basal reflector, making it difficult to detect thickness evolution of the ice and to correctly estimate vertical velocities. Variations in surface melt during ApRES deployments can substantially modulate the received signal strength on short timescales, and we therefore recommend using higher attenuator settings for deployments in such locations.